2019
DOI: 10.1039/c9ay00698b
|View full text |Cite
|
Sign up to set email alerts
|

Sheath-flow probe electrospray ionization (sfPESI) mass spectrometry for the rapid forensic analysis of human body fluids

Abstract: A novel method for the rapid,in situanalysis of fresh and dried human biological materials using sfPESI mass spectrometry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Previous research has demonstrated the effectiveness of sfPESI-MS in the analysis of biological materials, [17] but it has not yet been applied to the analysis of seminal fluid. This paper demonstrates the first application of ambient ionisation mass spectrometry to the forensic analysis of human semen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has demonstrated the effectiveness of sfPESI-MS in the analysis of biological materials, [17] but it has not yet been applied to the analysis of seminal fluid. This paper demonstrates the first application of ambient ionisation mass spectrometry to the forensic analysis of human semen.…”
Section: Introductionmentioning
confidence: 99%
“…Although these analytes have been detected in other bodily fluids, components such as spermine and choline are more abundant in semen, and previous analysis of body fluids by sfPESI has demonstrated different body fluids produce distinct mass spectra [17]. Urine was dominated by urea and creatinine, blood displayed strong signals for glucose/fructose, along with sodiated lipids, whereas saliva exhibited a complex mixture of low abundance acids.…”
mentioning
confidence: 99%
“…Initial sfPESI-MS data for the extraction solvent efficiency study were acquired using the interface configuration shown in Figure 1 (b), which has been reported elsewhere. 25 Whilst this configuration can obtain good quality sfPESI-MS data, it introduces variability in replicate measurements due to the position of the emitter with respect to 10970231, ja, Downloaded from https://analyticalsciencejournals.onlinelibrary.wiley.com/doi/10.1002/rcm.9422 by Loughborough University, Wiley Online Library on [25/10/2022]. See the Terms and Conditions (https://onlinelibrary.wiley.com/terms-and-conditions) on Wiley Online Library for rules of use; OA articles are governed by the applicable Creative Commons License the MS inlet varying when the emitter is manually refilled, which also reduces sample throughput.…”
Section: Sfpesi Emitter Construction and Interfacingmentioning
confidence: 99%
“…Human whole blood generally provides a complex background including many different species, such as proteins, lipids, salts, metabolites, etc., during ESI-MS analysis in either positive or negative ion mode, making the native blood sample a challenging matrix, and frequently requiring extensive sample preparation in order to enable measurements of targeted metabolite species. 25 For direct analysis of dried blood spots (DBSs) containing cocaine metabolites, the extraction solvent containing both modifiers, 0.1 % FA and 0.5 mM SA was compared to the 50 %v/v ethanol/water extraction solvent to determine whether reproducible data could be acquired from dried blood spots.…”
Section: Application To Dried Blood Spot Analysismentioning
confidence: 99%
“…MS methods tend to be destructive to the sample, however in a recent report [283] a new approach, sheath-flow probe electrospray ionisation MS was used, which allows stains to be sampled with no preparation or sample destruction bar the initial small amount taken. In the research which examined blood, saliva and urine, alterations were observed in the spectra over time suggesting that this approach could also be used to age a stain.…”
Section: Proteomementioning
confidence: 99%